Environmental Ecotheology Analysis from an Islamic Perspective Based on Ustadz Adi Hidayat's Lectures on YouTube and Its Implications for Islamic Religious Education Learning - Nur Aulia Sury; Zainuddin Syarif (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research examines the analysis of environmental ecotheology from an Islamic perspective based on Ustadz Adi Hidayat's YouTube lectures and its implications for learning of Islamic Religious Education (PAI). The present The study adopts a qualitative approach through library research approach type, with primary data presented in the form of Ustadz Adi Hidayat’s YouTube lectures as well as secondary data from references, scientific journal articles, Al-Qur'anic interpretations, and Islamic education literature. This study is limited to three problems, namely the concept of environmental ecotheology in Ustadz Adi Hidayat's YouTube lectures, environmental character education in the lectures, and environmental education strategies and their implications for PAI learning. The findings reveal that Islamic ecotheology in the lectures is built on the values ​​of monotheism, khalifah, amanah, and mizan which emphasize human responsibility in protecting the environment as part of worship. Environmental character education is delivered through a religious, contextual, and persuasive approach that emphasizes moral and spiritual awareness, while environmental education strategies are carried out through the integration of Al-Qur'anic and Hadith arguments, easy-to-understand communication, real-life examples, and the use of YouTube digital media. These findings indicate that Islamic ecotheological values ​​are relevant for integration into Islamic Religious Education (PAI) learning to strengthen students' religious character and environmental awareness in the digital age.